(untitled) (Veterinary Science, 2017)
The balanced food for laying hens may be contaminated with strains of fungi. The mycotoxins produced by them generate economic and productive problems in birds, such as decreased production, loss of overall state and death in extreme cases. The mycotoxins that affect more birds are aflatoxins produced by Aspergillus genus. The aim of this study was to assess the presence of aflatoxins in commercial and manufactured by farmers food for laying hens in the city of General Pico, La Pampa. The samples obtained were analysed by the ELISA method. In 2014 the presence of toxic levels of aflatoxin was determined in 77,8% of the analysed samples, while in the first half of 2015 out of 17 samples 64,7% of them were with toxic levels. The appearance of Aflatoxins in foodstuff is a result of the lack of quality controls of the raw materials and inadequate storage systems. These results determine the need for preventive measures for food handlers to avoid risks to which they are exposed. Meanwhile, the use of sequestrants is the most appropriate indication to reduce toxic effects on birds and avoid production losses